Kesiapan Rumah Sakit Indonesia Menghadapi Kompetensi Medicaltourism Di Asiatenggara - Diah Kumalasari (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Medical tourism or health tourism is a travel activity to get health services. Many Indonesian citizens choose to seek treatment abroad because Indonesia does not have a good health industry. This of course causes a reduction in state revenues in the health and tourism sectors. The writing of this article aims to determine the factors that influence people's interest in seeking treatment abroad so that they can be input for hospitals in Indonesia to be able to compete against medical tourism which is growing rapidly in Southeast Asia. The method used is to review the articles obtained from the database using inclusion criteria and keywords. The results obtained indicate that the factors that attract patients to get services in hospitals are high quality services, served by communicative medical personnel and staff, competent with international expertise and reputation, with short service times and affordable prices, availability of clear information, as well as safe and quality treatment outcomes.